The European Union towards Cohesion Challenges: What’s the Next Step? - Mouriki, Athanasia (HAPSc Policy Briefs Series, 2023)
Considering the important percentage of the annual budget spent on cohesion policy, this policy brief examines what it’s the cohesion policy of the EU, the problems the Union is facing in this domain and the actions that have been taken. Cohesion policy’s is aiming to eliminate imbalances between countries and regions. Nevertheless, a variety of issues observed on the achievement of this objection are being analyzed in this policy paper. The East-West divide, the North-South divide and the disparities between urban centers (capitals or large cities) and rural areas are the most severe issues. The “New Cohesion Policy 2021-2027” is trying to give concrete solutions. This policy brief recommends: More financial support, monitoring, spread the spirit of a united EU, avoid stigmatizing member states, and turning cohesion policy into an exclusive EU competence.